2015
DOI: 10.3389/fpsyg.2015.00954
|View full text |Cite
|
Sign up to set email alerts
|

The time course of emotional picture processing: an event-related potential study using a rapid serial visual presentation paradigm

Abstract: The present study recorded event-related potentials using rapid serial visual presentation paradigm to explore the time course of emotionally charged pictures. Participants completed a dual-target task as quickly and accurately as possible, in which they were asked to judge the gender of the person depicted (task 1) and the valence (positive, neutral, or negative) of the given picture (task 2). The results showed that the amplitudes of the P2 component were larger for emotional pictures than they were for neut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 84 publications
1
18
0
1
Order By: Relevance
“…For emotional faces, Calvo et al equally analyzed the LPP response to emotional faces, but the emotion modulation of the component was only seen in upper face half condition with an augmented LPP amplitudes for angry faces than those for the other expressions (neutral, happy, and surprise) [ 146 ]. The results supplied a further support for the previous findings regarding the relationship between emotion processing and LPP and additionally to some extent are supported by a subsequent study with RSVP involved [ 131 , 134 , 147 , 164 ]. Another ERP study employed the dynamical emotional faces which constituted emotional clips and also found the significant LPC difference among fear, anger, surprise, disgust, sad, and neutral (fear > the rest; anger and surprise > happy) [ 165 ].…”
Section: Emotion Processing Revealed By Erpssupporting
confidence: 86%
“…For emotional faces, Calvo et al equally analyzed the LPP response to emotional faces, but the emotion modulation of the component was only seen in upper face half condition with an augmented LPP amplitudes for angry faces than those for the other expressions (neutral, happy, and surprise) [ 146 ]. The results supplied a further support for the previous findings regarding the relationship between emotion processing and LPP and additionally to some extent are supported by a subsequent study with RSVP involved [ 131 , 134 , 147 , 164 ]. Another ERP study employed the dynamical emotional faces which constituted emotional clips and also found the significant LPC difference among fear, anger, surprise, disgust, sad, and neutral (fear > the rest; anger and surprise > happy) [ 165 ].…”
Section: Emotion Processing Revealed By Erpssupporting
confidence: 86%
“…Electro- and magnetoencephalographic (EEG/MEG) studies have revealed that early (∼80–120 ms after stimulus onset) ( Keil et al, 2002 ; Olofsson and Polich, 2007 ; Feng et al, 2014 ; Zhu et al, 2015 ) and mid-latency (∼120–300 ms) ( Liddell et al, 2004 ; Williams et al, 2004 ; Balconi and Lucchiari, 2005b , 2007 ; Kiss and Eimer, 2008 ; Pegna et al, 2008 ; Kim et al, 2013 ; Nakajima et al, 2015 ) event-related potentials and fields (ERPs/ERFs) in response to both subliminal and supraliminal negative material differ from those to positive or neutral material. For example, Liddell et al (2004) recorded ERPs in response to subliminally (10 ms) and supraliminally (170 ms) presented backward-masked fearful and neutral faces.…”
Section: Introductionmentioning
confidence: 99%
“…By using emotional stimuli including emotional words (Ponz et al, 2014 ), emotional pictures (Carretié et al, 2001 ; Delplanque et al, 2004 ; Huang and Luo, 2006 ; Zhu et al, 2015 ), and even esthetic images (Wang et al, 2012 ; Muñoz and Martín-Loeches, 2015 ), numerous affective ERP studies have demonstrated that the frontal P200 amplitudes elicited by negative stimuli are significantly greater than those elicited by positive stimuli. Generally, the P200 component has been linked to early attention according to affective features of the stimuli to be attended.…”
Section: Discussionmentioning
confidence: 99%